Penggunaan Strategi Heuristik Model Polya dalam Meningkatkan Kompetensi Pembelajaran Matematika Keuangan Ditinjau dari Pengetahuan Awal Mahasiswa Universitas Timor - Justin Eduardo Simarmata; Lailin Hijriani (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
The research aims to depict students’ ability in solving mathematical problems based on Polya’s heuristic. Descriptive qualitative was used as a method in this research. Data were collected by observation, test, and interview. Based on the result of analysis obtained that the students with low level prior knowledge think heuristically in solving the problem solving test. For the students with medium level prior knowledge, the students think algorithmically and couldn’t solve the problem solving test imperfectly. Furthermore, the students with high level prior knowledge think algorithmically in solving the problem solving mathematics test and the other words, the students could solve the problem solving test well and fluently.